Type-Specific Customized eSports for Promoting Overall Health in the Elderly - Byeong Hwan Jeon (The Asian Journal of Kinesiology)
OBJECTIVES With the acceleration of global population ageing, issues such as physical and mental health decline, cognitive deterioration, and social isolation among the elderly have emerged as important social challenges. This study aimed to examine the potential and future directions of eSports tailored to the elderly in promoting overall health by types of eSports. METHODS This study employed a narrative review approach to examine the application of various types of e-sports for the elderly, which limits the reproducibility and generalizability of findings. The absence of a predefined systematic search strategy, explicit inclusion and exclusion criteria, and standardized quality assessment procedures may have introduced selection bias and reduced the comprehensiveness of the literature review1. Despite these methodological limitations, the cognitive and brain health effects of each eSports type were analyzed, and practical implementation strategies were discussed. RESULTS Distinct eSports types—including digital board/strategy games, action/shooting games, sports/racing games, exergames, puzzle/functional games, and cooperative/community-based games—offer unique cognitive, physical, and psychosocial benefits for older adults. Evidence from previous studies demonstrates that tailored eSports programs can improve cognitive function, brain health, social engagement, and quality of life in the elderly. Key factors for effective implementation include user-friendly interface design, content difficulty adjustment, expansion of community-based programs, and robust policy support. CONCLUSIONS Customized eSports for the elderly have specialized advantages in promoting cognitive function and brain health, depending on the type. While showing similar effects such as cognitive function enhancement, physical health promotion, emotional stability, and social interaction promotion, each type has its own unique advantages and application factors. For e-sports to be successfully disseminated among the elderly, user-centered design, adaptive content, regular community operation, and multidisciplinary policy support are necessary.